PENGARUH MODEL INSTRUKSIONAL KOOPERATIF TIPE CORE TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Hendri Eka Jaya Putra; Hendar Ahmad Wibisono (Akademika, 2021)
The low learning outcomes of mathematics at junior high school level students are due to the low ability of students to use and assess the relationship between mathematics topics and organize the information obtained. One of the learning models with the discussion method that encourages students to use and assess the relationship between mathematical topics and organize the information obtained is the cooperative CORE (Connecting, Organizing, Reflecting, and Extending) learning model. The purpose of this study was to analyze the improvement of students' mathematical representation abilities through CORE models and analyzing differences in mathematical representation abilities between students using a cooperative CORE model with students using the learning method with the scientific approach, as well as to see student responses to the cooperative learning model type CORE. The method used is the Quasi Experimental Design method with type Non equivalent Control Group Design, with a population of all class VIII students of Al Ihsan Legenda Bekasi Junior High School for the 2019/2020 school year. The sampling technique used purposive sampling. The instruments used were questionnaire sheets and essay tests in accordance with the indicators of mathematical representation in the Functions. The results showed that there were differences in mathematical representation abilities between students who used the cooperative CORE model by using the learning method with a scientific approach, as well as student responses after using the CORE cooperative, make students more active and make it easier for students to learn the material and can improve student learning outcomes.